Dealing with senior citizens in Malaysia: a critical reading of the related Qur’anic verses and the prophetic tradition (Hadīth) - Jani, Mohd. Shah; Fatah Yasin, Raudlotul Firdaus (International Islamic University Malaysia, 2017)
The majority of researches on senior citizens of Malaysia is mainly related with the urgent need to establish a comprehensive healthcare system and services that may incorporate the rights of the aging population of Malaysia for them to lead a healthy and quality life. Undoubtedly, such a study is missing some of the other major issues immediately connected with the older population that have been a core subject of gerontology studies, a newly independent social science discipline that is now being introduced in few institutes of higher learning in Malaysia. This present research does not claim to be a comprehensive study of all the issues related to the aging population in Malaysia. It only seeks to fill in the vacuum not highlighted in the current Islamic literatures. Many of these literatures are merely repetitions of the classical tafsīr and fiqh (jurisprudence) works, which are usually confined to a particular emphasis on the responsibility of children to look after their elderly parents. It must be recognized that the contribution of those literatures is certainly significant as they may provide an ethical framework for the Islamic principle of dealing with senior citizens that the duty to looking after the welfares and wellbeing of the older people is strictly placed upon the responsibility of their children. This research is contented to argue that such a view is not fully compatible with the objectives of the Sharīʿah (maqāṣid al-sharīʿah), and is no longer attainable if looked at from the perspective of today’s dynamic development and change of the socio-economic and demographic contexts in Malaysia. This research is therefore conducted to revisit those traditional interpretations with the application of critical exegetical reading upon some of the older people-related texts from either the Qurʾān or ḥadīth. Finally, this research is hoping to highlight the importance of integrating Islamic code of ethics towards developing a comprehensive system and policy in dealing with the issues of aging population in Malaysia.